PENINGKATAN PRODUKTIVITAS PEDAGANG BAKSO ECBRAN MELALUI PENGGUNAAN MESIN PENGGILING DAN PENCAMPUR BAHAN BAKSO - Nurhadiyanto, Didik; Sudiyatno, Sudiyatno; Said, Suprato Rachmad (Universitas Negeri Yogyakarta, 2005)
Mixerandmillermachinesforball soupingredientarewidelyused.Mostlythemachineshavedisadvantagessuch asthey areexpensive (about10millionsrupiah),havea bigconstructionandneedabigpower(withl0HP dieselengine).Themachinesarelostbig energyduetofnctionbetweenthemixerand itslid.Thisprogrammeanttoproduceacheaperandsmallermixer andmillermachine.To dothisprogram,stepsweremadeasfollows:(l)designinga newconstructionbasedontheexistedmachines,(2)modificationwasconcentratedon minimizingfrictionoccurredinthemachine, (3)usinganelectricmotortomakea simplerconstruction, (4)upgradingtoimprovethenew machine'sperformance.Fromthetesting,itcanbe shownthat:(l)speedofthe motoris2.800rpm,speedof themixeris 420rpm,speedof themixing processis280rpm.(2)themachineis 1.442m long,0.85m wideandr.410mhigh,(3) one mixing processneeds3 kgofmeat, Ikg of wheatflourandspices(garlic,saltandpepper),(4)meatmilling processneeds3 minutes,mixingof all ingredientneeds7minutesandprocessof settingmachineandservicingone consumerneeds2minutes,so thehallprocessesneedsabout12 minutes,and(5)the newmachinehasa higherefficiencyandtheproducthasagoodqualityappearancewithastrong meatflavorandno meatfiberleft.Keywords:meat,miller,mixer,andmeatball soup